Adsorption of Dye Olive BGL Using Two Different Samples of Activated Carbon by Static Batch Method - Kant, Rita (Asian Journal of Chemistry, 2012)
The removal of dye olive BGL using two different samples of activated carbon by static batch method was studied. Experimental data on optical density of blank solutions of different concentrations ranging from 10-100 mg/L and optical density of solutions after adsorption on activated carbon samples were taken and analyzed. Calibration curves were plotted and the amount of dye adsorbed was calculated. The data was fitted to Langmuir and Freundlich isotherms for two different carbon samples and different concentration values. Constants were calculated from the slope and intercept values of the isotherms. Coefficient of correlation R2 and standard deviation were also recorded. The data fitted well to the isotherms. Carbon sample C1 showed higher potential to adsorb the dye olive BGL at lower concentrations of the solution whereas carbon sample C2 showed better results at higher concentration. Carbon sample C2 showed better adsorption in acidic pH as compared to in alkaline pH. From the analysis of the data it is shown that activated carbon has good capacity to remove the textile dye from the residue water.